Determination of the heat transfer coefficient of a rotary film evaporator with a heating film-forming element - Zahorulko, Andrii; Загорулько, Андрій Миколайович; Zagorulko, Aleksey; Загорулько, Олексій Євгенович; Cherevko, Oleksander; Черевко, Олександр Іванович; Dromenko, Olena; Дроменко, Олена Борисівна; Solomon, Alla; Соломон, Алла Миколаївна; Yakobchuk, Roman; Якобчук, Роман Леонідович; et al. (ПП "ТЕХНОЛОГІЧНИЙ ЦЕНТР" Український державний університет залізничного транспорту, 2021)
A model of a rotary film evaporator with a film-forming element with a reflective heated surface has been developed. This will allow stabilizing the hydraulic movement of the cut wave flow due to the reflective surface of the geometric shape for the forced direction of the cut raw material to the heating surface. Autonomous heating of the reflective surface additionally provides a temperature effect in the conditions of movement of particles of raw materials after cutting. The analysis of the experimental and theoretical parameters of heat transfer made it possible to substantiate the criterion equation for determining the heat transfer coefficient of an evaporator with the proposed film-forming element and a reflective heated surface for calculating the coefficient from the working surface to the raw material. The resulting equation takes into account the influence of the vertical component of the motion of the raw material film, centrifugal movement during the rotation of the film-forming element, mixing of the boiling film of the raw material with steam bubbles, and the geometric characteristics of the film-forming blade on the hydrodynamic flow of the raw material. The calculation of the rotary-film evaporator was carried out using the criterion equation and the obtained useful heat exchange surface – 0.75 m2. The specific metal consumption in a rotary film evaporator with a film-forming element having a reflective surface is 57 kg/m2, compared to the vacuum evaporator traditionally used in canning industries (410 kg/m2), which is 7.1 times less. The duration of the temperature effect on the raw material is also reduced: a rotary film evaporator – 200 s and 3600 s in a traditional apparatus. The data obtained will be useful for the design of rotary-film devices of different geometric parameters using articulated blades with a reflective plate. Розроблено модель роторного-плівкового випарника з плівкоутворюючим елементом, який має відбивальну обігріваєму поверхню. Таке рішення запропоновано для стабілізації гідравлічного руху зрізаємої хвильової течії за рахунок відбивальної поверхні певної геометричної форми для примусового спрямовування зрізаємої сировини на нагрівальну поверхню. Автономний підігрів відбивальної поверхні додатково забезпечує температурний ефект в умовах переміщування часток сировини після зрізання. У результаті аналізу експериментально-теоретичних параметрів теплообміну обґрунтовано критеріальне рівняння коефіцієнта тепловіддачі випарника з запропонованим плівкоутворюючим елементом, який має відбивальну обігріваєму поверхню для розрахунку коефіцієнта тепловіддачі від робочої поверхні до сировини. Отримане рівняння враховує вплив вертикальної складової руху плівки сировини, відцентрове переміщення при обертанні плівкоутворюючого елемента, перемішування киплячої плівки сировини пухирцями пари, геометричних характеристик плівкоутворюючої лопаті на гідродинамічний плин сировини. Здійснено розрахунок роторного-плівкового випарника з використанням критеріального рівняння та отримано корисну поверхню теплообміну – 0,75 м2. Питома металоємність в роторно-плівковому випарнику з плівкоутворюючим елементом, що має відбивальну поверхню становить 57 кг/м2 порівняно з традиційно використовуваним в консервних виробництвах вакуум-випарним апаратом 410 кг/м2, що у 7,1 раз менше. Також зменшується тривалість температурного впливу на сировину: роторно-плівковий випарник – 200 с та 3600 с у традиційному апараті. Отримані дані будуть корисні для проєктування роторно-плівкових апаратів різних геометричних параметрів, що використовують шарнірні лопаті з відбивальною пластиною.
Визначення коефіцієнта тепловіддачі роторно-плівкового випарника з гріючим плівкоутворюючим елементом
Keywords: heat transfer coefficient; коефіцієнт тепловіддачі; rotary film evaporator; роторно-плівковий випарник; criterion equation; критеріальне рівняння; film-forming element; плівкоутворюючий елемент; organic raw materials; органічна сировина